Triglyceride/HDL-Cholesterol Ratio as an Index of Intracranial Atherosclerosis in Nonstroke Individuals - Woo, Min-Hee; Lee, Kee Ook; Chung, Darda; Choi, Jung-Won; Kim, Sang-Heum; Oh, Seung-Hun (Frontiers in Neurology, 2021)
Background: Triglyceride (TG)/high-density lipoprotein cholesterol ratio (THR) is a marker of dyslipidemia, and high THR is associated with an increase in cardiovascular events. In the present study, whether THR was associated with various markers of cerebral vascular pathologies, atherosclerosis of major cerebral arteries, including large artery atherosclerosis (LAA) and cerebral small vessel disease (SVD), in neurologically healthy individuals was investigated. Methods: Vascular risk factors, brain magnetic resonance imaging (MRI) scans, and MR angiograms of 851 study subjects were evaluated. Findings of extracranial atherosclerosis (ECAS) and intracranial atherosclerosis (ICAS) were considered indices of LAA based on brain MR angiograms. The presence of silent lacunar infarct (SLI) and white matter hyperintensities (WMHs) were evaluated as indices of SVD based on brain MRIs. Results: Subjects with ICAS (odds ratio, 1.83; 95% confidence interval, 1.06–3.16; P = 0.03) were significantly more likely to have high THR tertile (THR > 2.06) than low THR tertile (THR < 1.37) after adjusting for cardiovascular risk factors. THR was higher in subjects with multiple ICAS lesions than in those with single ECAS or without ICAS lesions. Associations among THR tertiles in ECAS, SLI, and WMHs were not significant. Conclusion: In the present study, a positive association between high THR and the development of ICAS was observed in neurologically healthy participants.